2021
DOI: 10.1101/2021.01.08.426018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epstein-Barr Virus Induced Cytidine Metabolism Roles in Transformed B-cell Growth and Survival

Abstract: Epstein-Barr virus (EBV) is associated with 200,000 cancers annually, including B-cell lymphomas in immunosuppressed hosts. Hypomorphic mutations of the de novo pyrimidine synthesis pathway enzyme cytidine 5’ triphosphate synthase 1 (CTPS1) suppress cell mediated immunity, resulting in fulminant EBV infection and EBV+ central nervous system (CNS) lymphomas. Since CTP is a critical precursor for DNA, RNA and phospholipid synthesis, this observation raises the question of whether the isozyme CTPS2 or cytidine sa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Similarly, the de novo pyrimidine synthesis enzyme dihydroorotate dehydrogenase (DHODH) generates CoQH 2 , which can be used to quench lipid ROS within the mitochondrial inner membrane (54). We recently identified that EBV highly induces DHODH and de novo pyrimidine activity in newly infected B-cells (55). Furthermore, GTP cyclohydrolase 1 (GCH1) can suppress ferroptosis via the generation of the radical-trapping antioxidant tetrahydrobiopterin (BH4) (56).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the de novo pyrimidine synthesis enzyme dihydroorotate dehydrogenase (DHODH) generates CoQH 2 , which can be used to quench lipid ROS within the mitochondrial inner membrane (54). We recently identified that EBV highly induces DHODH and de novo pyrimidine activity in newly infected B-cells (55). Furthermore, GTP cyclohydrolase 1 (GCH1) can suppress ferroptosis via the generation of the radical-trapping antioxidant tetrahydrobiopterin (BH4) (56).…”
Section: Discussionmentioning
confidence: 99%
“…Other significant metabolites included the nucleotide cytosine, and related nucleosides cytidine and 2'-deoxy-cytidine, key building blocks in the creation of DNA and RNA. More recently, cytidine metabolism was revealed to be important during EBV virus induced B cell transformation, growth, and survival (51), highlighting its importance in gammaherpesvirus induced oncogenesis. The purine nucleoside 1-methyladenosine showed a significant increase during MHV-68 infection.…”
Section: While Metabolomics Analysis Of Host Cells During Viral Infec...mentioning
confidence: 99%